Interest Patterns Measurement Application for Vocational High School Students - Kumaidi, K; Kurniawan, Yogiek Indra; Farida, Rahayu (Universitas Muhammadiyah Surakarta, 2017)
Interest patterns are the characteristic of a student's interest in which the student wishes to engage in a particular field. The pattern of interest of students in vocational high school in Indonesia should be known to obtain an appropriate career based on the student's interest. To reveal the pattern of interest, an instrument based on the Holland theory has been developed in Indonesia. Nevertheless, the test is performed manually using pencil and paper thus there are some ineffectiveness during the implementation. Moreover, it requires longer time for data processing and is susceptible to error. Therefore, a computer-based application that can measure the interest patterns is built. With the existence of this computer-based application, data processing can be done quickly and accurately without any errors and can be accessed anywhere and anytime. This research found that the use of the application can support the effectiveness and efficiency of the test in recognizing the interest pattern of a student.